The Construction of Goshute Political Identity: Negotiation of Voice Regarding Nuclear Waste Policy Development - Clarke, Tracylee (Frontiers in Communication, 2017)
This article examines the relationship between political identity and voice through an analysis of conflict between members of the same Native American nation over the development of environmental policy. Grounding this study in the work of Paul Ricoeur and his theory of narrated identity, and using Senecah’s “Trinity of Voice” as an analytical framework, I examine communication and negotiation of voice among members of the Skull Valley Goshute tribe regarding the storing of nuclear waste on their reservation. I argue that tribal members’ identities are constructed through political narratives about voice (or lack thereof) complicating their sense of self and creating a complex forum for tribal nuclear waste policy development and decision-making. This article contributes to our theoretical understanding of political voice and identity, revealing its implications for nuclear waste policy development. Further, it provides a deeper understanding of the complexities of environmental conflicts within Native American communities.